Propuesta de articulación del sistema integrado de gestión HSEQ y el modelo integrado de planeación y gestión en una entidad del estado colombiano (2021)
In Colombia, public entities are required to implement their management systems, which serve as a methodology to guarantee quality in the provision of their services, focusing on meeting the needs of value groups and interested parties. The Management System can be composed of one or more management systems based on certifiable standards, depending on the mission of the entity, and each system establishes its own requirements which entities must meet to achieve their implementation. With the aim of facilitating these processes of implementation of management systems, the Integrated Planning and Management Model - MIPG emerged in Colombia, as a guiding tool that facilitates entities, the process of implementation or updating of their systems quality management in a comprehensive manner.